Analysis of Media Framing on Indonesian Constitutional Court’s Decision Regarding Presidential and Vice Presidential Age Limits - Permadi, Didi (IHSA Institute, 2024)
The determination of the age limit for presidential and vice-presidential candidates is a crucial issue in the dynamics of Indonesian politics. The Constitutional Court's decision regarding this age limit has profound implications for the political landscape and the political participation opportunities for individuals aspiring to run for president or vice president. This research aims to understand the framing constructions of Tempo.co and Viva.co.id, two mass media outlets, regarding the coverage of the Constitutional Court's decision on the minimum age limit for presidential and vice-presidential candidates. The method employed in this research was based on the framing concept by Pan and Kosicki, which consisted of four main elements: syntax, script, thematic, and rhetoric. The results of the study show that Tempo.co framed this coverage by emphasizing the contrasting (negative) aspects of the decision. In contrast, Viva.co.id highlighted more positive aspects of the decision and focused on reporting the positive impacts of the Constitutional Court's decision